Analysis of Amelogenin and Sex-determining Region on Y Chromosome Genes Obtained from Pulpal Tissue for Sex Estimation by using Multiplex Polymerase Chain Reaction - Baban, Mohammed Taha Ahmed; Mohammad , Dena Nadhim; Al-Rawi , Natheer (Kurdistan Journal of Applied Research, 2023)
In forensic odontology, Amelogenin and Sex-Determining Region on Y chromosome genes are commonly used for sex identification. Nevertheless, the amplification of both of these genes encounters limitations in determining sex, primarily due to deletions observed in certain racial groups and the influence of genetic disorders on these genes. This research aims to assess the precision of simultaneously amplifying both genes using multiplex polymerase chain reaction on samples derived from teeth that have been subjected to various forensic conditions. In this study, a total of 70 teeth, comprising 35 males and 35 females, were utilized, and all samples underwent genetic analysis to determine sex following exposure to different forensic scenarios. The findings revealed that both the quantity and quality of genetic material were reduced when exposed to harsh environmental conditions. Notably, the amplification of the sex-determining region on the Y chromosome gene outperformed the amplification of Amelogenin and achieved a sex-determination accuracy rate of 100%. In conclusion, dental pulp serves as a valuable source of genetic material even after exposure to diverse environmental conditions, and it can effectively be used for sex estimation purposes.